The effect of the global COVID-19 pandemic on the secondary sector in Côte d`Ivoire - Dogo Armand Dago; Yu Pei (Cogent Economics & Finance, 2024)
This research investigates the repercussions of the global COVID-19 pandemic on the secondary sector of Côte d'Ivoire during the period 2020-2022. Using two-stage generalized random effects (G2SLS) instrumental variable (IV) models is a statistical method used in econometrics, particularly in the context of instrumental variable (IV) models. In the context of the study, G2SLS helps in establishing the causal impact of the COVID-19 pandemic on the secondary sector while accounting for potential endogeneity issues. This study comprehensively analyzes the effects of COVID-19, and economic performance, country factors, structural characteristics, responses to fiscal and monetary policies, and overall growth in industrial production. Expanding its focus to a comparative analysis with Nigeria, Egypt, South Africa, China, and France, this research uses a robust econometric approach to unravel the complex dynamics of the secondary sector. From a cross-national perspective, this study provides nuanced insights for policymakers and stakeholders. The findings of this study could contribute to secondary sector public policy strategy-making and instruments definitions to resist similar threats. This study examines the effects of the COVID-19 pandemic on Côte d'Ivoire's secondary sector. By employing advanced econometric models, it assesses both immediate disruptions and long-term structural changes in industrial production and employment. The research also includes comparative analysis with other countries to provide broader insights. The findings highlight the need for robust public policies and strategies to strengthen the sector's resilience against future crises, emphasizing the importance of economic diversification and adaptive policy measures for sustainable recovery and development.
Keywords: 330; COVID-19 pandemic; secondary sector performance; economic performance; economicgrowth; Côte d'Ivoire; Industrial production